Peran Al-Qur’an dalam Membangun Toleransi dan Kerukunan Antar Umat Beragama di Kota Medan - Alfadillah, Muhammad Rafly; Andy, Safria (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Nowadays, inter-religious conflicts are prone to occur in various regions, including Medan City. Burning houses of worship, prohibiting worship, and disturbing the solemnity of other people's worship are conflicts that often occur. Tolerance and harmony are the main weapons in creating peaceful living among communities. This is what is built by the Medan City Religious Harmony Forum. The Forum for Religious Harmony (FKUB) of Medan City maintains tolerance and harmony among religious communities through educative, dialogical approaches and interfaith deliberations to build mutual understanding and resolve potential conflicts peacefully. This approach is in line with the principle of taʿāruf (knowing each other) in QS. Al-Hujurat verse 13, which according to the mufasir Sahl al-Tustari, shows that diversity is a means to understand each other and perfect ourselves, not to be contradicted. The results of research in the community show that Qur'anic values such as QS. Al-Kāfirūn: 6, QS. Al-Baqarah: 256, and QS. Al-Hujurat: 13 have been internalized in the lives of interfaith communities in Medan City. The findings from three different areas (Muslim-majority, non-Muslim, and balanced) show that tolerance has become part of the community's social culture. Thus, the Qur'an is not only a guide to faith but also a guideline to build a peaceful and harmonious plural society. This research uses descriptive qualitative methodology with a thematic interpretation approach using theological-normative perspectives.